miR-224-5p and miR-545-5p Levels Relate to Exacerbations and Lung Function in a Pilot Study of X-Linked MicroRNA Expression in Cystic Fibrosis Monocytes - McKiernan, Paul J.; Molloy, Kevin P.; Glasgow, Arlene M. A.; McElvaney, Noel G.; Greene, Catherine M. (Frontiers in Genetics, 2021)
Altered microRNA expression patterns in bronchial brushings from people with versus without cystic fibrosis (CF) relate to functional changes and disease pathophysiology. The expression of microRNAs encoded on the X chromosome is also altered in peripheral blood monocytes of p. Phe508del homozygous versus non-CF individuals. Here we investigate whether levels of the top seven X-linked microRNAs (miR-224-5p, miR-452-5p, miR-450b-5p, miR-542-3p, miR-450a-5p, miR-424-5p, and miR-545-5p) that are significantly increased over 1.5 fold in CF versus non-CF monocytes correlate with lung function. CD14+ monocytes were isolated from males and females with (n = 12) and without cystic fibrosis (n = 12) and examined for the expression of X-linked microRNAs by qRT-PCR array. MicroRNA target mRNA levels were quantified using qRT-PCR. Clinical correlations with lung function data were analysed in the CF cohort. Increasing levels of miR-545-5p correlated moderately with FEV1% predicted (r = -0.4553, p > 0.05) and strongly with exacerbation rate (r = 0.5858, p = 0.0483). miR-224-5p levels were significantly higher in the severe (FEV1 <40%) versus mild (FEV1 ≥80%, p = 0.0377) or moderate (FEV1 40–79%, p = 0.0350) groups. MiR-224-5p expression inversely correlated with lung function (FEV1%: r = -0.5944, p = 0.0457) and positively correlated with exacerbation rates (r = 0.6139, p = 0.0370). These data show that peripheral blood monocyte miR-545-5p and miR-224-5p levels correlate with exacerbation rate, whilst miR-224-5p levels also correlate with lung function in cystic fibrosis.